ANISEED 2015: a digital framework for the comparative developmental biology of ascidians. Issue Volume 44:Issue D1(2016) (29th September 2015) - Brozovic, Matija; Martin, Cyril; Dantec, Christelle; Dauga, Delphine; Mendez, Mickaël; Simion, Paul; Percher, Madeline; Laporte, Baptiste; Scornavacca, Céline; Di Gregorio, Anna; Fujiwara, Shigeki; Gineste, Mathieu; et al.
Abstract: Ascidians belong to the tunicates, the sister group of vertebrates and are recognized model organisms in the field of embryonic development, regeneration and stem cells. ANISEED is the main information system in the field of ascidian developmental biology. This article reports the development of the system since its initial publication in 2010. Over the past five years, we refactored the system from an initial custom schema to an extended version of the Chado schema and redesigned all user and back end interfaces. This new architecture was used to improve and enrich the description of Ciona intestinalis embryonic development, based on an improved genome assembly and gene model set, refined functional gene annotation, and anatomical ontologies, and a new collection of full ORF cDNAs. The genomes of nine ascidian species have been sequenced since the release of the C. intestinalis genome. In ANISEED 2015, all nine new ascidian species can be explored via dedicated genome browsers, and searched by Blast. In addition, ANISEED provides full functional gene annotation, anatomical ontologies and some gene expression data for the six species with highest quality genomes. ANISEED is publicly available at: http://www.aniseed.cnrs.fr .